PENGARUH KOMUNIKASI INTERPERSONAL CUSTOMER SERVICE TERHADAP LOYALITAS NASABAH BANK SYARIAH INDONESIA KCP TANAH TINGGI - Irwanda, Andri; Abdurahman, Ade Irfan; Pradesti, Ajeng (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2024)
The purpose of this study is to determine whether there is an influence between interpersonal communication on customer loyalty of Bank Syariah Indonesia KCP Tanah Tinggi, and measure the extent of the role or relationship of interpersonal communication on customer loyalty of Bank Syariah Indonesia KCP Tanah Tinggi. This type of research is correlational with a quantitative approach. The results of the study were obtained through hypothesis testing using the t test and obtained the results of a significant influence between interpersonal communication on the loyalty of Bank Syariah Indonesia customers with the results of the calculation of r count (2-tailed) of 0.000 <0.05 so that it was confirmed that Ha was accepted and Ho was rejected. Then the correlation between variable X (Interpersonal Communication) to variable Y (Customer Loyalty) can be seen from the results of the Spearman Rank correlation test which shows a value of 0.693 with a significance of 0.000> 0.05, it can be concluded that the strength of the correlation is 69.3% and has a positive and strong relationship